Bullous pemphigoid--management of a patient with oral and skin lesions - Ali, T.B.; Zain, R.B.; Adam, B.A. (1994)
A case of bullous pemphigoid with extra-oral and intraoral lesions in a 60-year-old female is reported. Diagnosis is based on histopathology and direct immunofluorescence, and the treatment regime described included oral prescription of prednisolone and topical application of a mixture of fluocinonide ointment and triamcinolone acetonide in Orabase on the oral lesions.